2018
DOI: 10.1177/1043986218770003
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting a Criminological Classic: The Cycle of Violence

Abstract: There is a growing "replication crisis" in the social and behavioral sciences, where original research across a wide array of substantive areas has failed to replicate when conducted by others. This problem highlights the importance of carefully revisiting original research-particularly studies that have exerted a significant influence over the field. Accordingly, in the present study, we subject Widom's classic work, "The Cycle of Violence," to a rigorous empirical reproduction and extension. We subjected her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 62 publications
0
3
2
Order By: Relevance
“…With respect to physical and psychological violence in particular, our results confirm that each of the three violence experiences promote violent behavior. Contrary to some earlier findings according to which the link between childhood experience of physical abuse and violence in adulthood do not survive robustness checks (Myers et al, 2018), we found that frequent exposure to physical violence was a strong predictor of physically violent behavior. Myers et al (2018) on the other hand, showed that childhood neglect (instead of physical abuse) was the most robust predictor of adult violence (Myers et al, 2018).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…With respect to physical and psychological violence in particular, our results confirm that each of the three violence experiences promote violent behavior. Contrary to some earlier findings according to which the link between childhood experience of physical abuse and violence in adulthood do not survive robustness checks (Myers et al, 2018), we found that frequent exposure to physical violence was a strong predictor of physically violent behavior. Myers et al (2018) on the other hand, showed that childhood neglect (instead of physical abuse) was the most robust predictor of adult violence (Myers et al, 2018).…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to some earlier findings according to which the link between childhood experience of physical abuse and violence in adulthood do not survive robustness checks (Myers et al, 2018), we found that frequent exposure to physical violence was a strong predictor of physically violent behavior. Myers et al (2018) on the other hand, showed that childhood neglect (instead of physical abuse) was the most robust predictor of adult violence (Myers et al, 2018). Nevertheless, our results are in line with previous findings showing an association between one's own experience of and the perpetration of physical violence thereof (Dodge et al, 1990;Widom & Maxfield, 2001).…”
Section: Discussioncontrasting
confidence: 99%
“…Even though adolescent victimization did not seem to impact high-risk youth negatively in the long term, an earlier experience with victimization could have (Keiley, Howe, Dodge, Bates, & Pettit, 2001;Norris & Murrell, 1988). To be sure, childhood victimization is known to carry profound negative consequences that extend into adulthood (Danese et al, 2016;Fry et al, 2018;Maxfield & Widom, 1996), and yet there is still substantial variation in how maltreated children fare as adults-variation that is not well understood (Jaffee, Caspi, Moffitt, Polo-Tomas, & Taylor, 2007;McGrath, Nilsen, & Kerley, 2011;Myers, Lloyd, Turanovic, & Pratt, 2018). By using rich data on children's early lives (Belsky, 1993), future work should be aimed at examining heterogeneity in the consequences of childhood victimization to determine whether similar patterns emerge.…”
Section: Discussionmentioning
confidence: 99%
“…As noted, based on the experience of the AJPS verification policy, it is rare for an independent team to reproduce the results on first attempt, even with access to documentation far more detailed than what was available to Maxwell et al Given the circumstances, this level of success in the reproduction adds a great deal of confidence in the integrity of Sampson et al's (1997) influential article. "The Cycle of Violence" by Cathy Spatz Widom (1989) was the focus of replication in the article by Myers, Lloyd, Turanovic, and Pratt (2018). This is another highly cited criminological classic published in the journal Science.…”
Section: Organized Skepticismmentioning
confidence: 98%
“…“The Cycle of Violence” by Cathy Spatz Widom (1989) was the focus of replication in the article by Myers, Lloyd, Turanovic, and Pratt (2018). This is another highly cited criminological classic published in the journal Science .…”
mentioning
confidence: 96%